EFFECT OF CURRENT RATIO, DEBT-TO-EQUITY RATIO, RETURN ON ASSETS, AND COMPANY SIZE ON THE RISK OF BUSINESS FAILURE (Empirical Study of Food and Beverage Companies Listed on the Indonesia Stock Exchange in 2019-2021) - Prakoso, Nugroho Agung; Harahap, Muhammad Nasim; Nasution, R. (Jurnal Ilmiah Wahana Pendidikan, 2024)
The global impact of the Covid-19 pandemic has led to market crises, investor losses, and business closures. Understanding a company's financial health is crucial, particularly during economic uncertainty. This study uses signal theory to identify factors that indicate business failure or bankruptcy. Specifically, it examines the risk of business failure in food and beverage companies listed on the Indonesia Stock Exchange and identifies the associated risk factors. Multiple linear regression analyses the relationships between variables, including the risk of business failure (proxied by Z Score), current ratio, debt to equity ratio, return on assets, and company size. The study encompasses 156 companies in the food and beverage subsector from 2019-2021 and utilizes secondary data from the Indonesian Stock Exchange's annual financial reports. The findings demonstrate that the variables current ratio, debt-to-equity ratio, return on assets, and firm size simultaneously influences the risk of business failure significantly. However, when examined partially, the current ratio and company size did not significantly impact. In contrast, the debt-to-equity ratio and return on assets are significant risk factors for business failure in the food and beverage subsector listed on the Indonesia Stock Exchange between 2019-2021.